Following the Wave or Riding Alone? A Decade of Thematic Evolution at SBBD vs. VLDB - de Melo, Tiago (Anais do Simpósio Brasileiro de Banco de Dados (SBBD); 2026: Anais do XLI Simpósio Brasileiro de Bancos de Dados, 2026)
Does SBBD mirror the global database research agenda or cultivate a distinct, locally shaped identity? We study this using large-scale topic modeling of a decade of publications: 489 SBBD and 3,036 VLDB full-text papers from 2016–2025. Applying BERTopic with multilingual embeddings and LLM-assisted label refinement, we extract 31 SBBD and 35 VLDB topics and align them semantically. We observe three patterns: (1) convergence, with 58% of SBBD topics matching VLDB topics, notably in data management, privacy, and NLP; (2) temporal lag, with SBBD adopting mainstream trends 1–4 years after their VLDB peak; and (3) divergence, with 13 SBBD-only topics highlighting a strongly applied, Brazil-centric identity. We conclude with a forward-looking research agenda for SBBD structured around five strategic directions.